Social Interest, Linguistic Indifférence - Sankoff, David (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1994)
Based on the human interests underlying sociolinguistic description and interpretation, the author traces the epistemological imperatives of the study of syntactic variation through data and method to the theoretical preoccupation with form-function polyvalence. The ultimate locus of all syntactic or sociological claims of a theoretical or methodological nature derives from the communicative intentions of a speaker at the moment in dicourse where more than one referentially or functionally equivalent structure is accessible. We situate this moment in a social scientific critique of linguistic ideologies.